The Inflammatory Chemokine CCL5 and Cancer Progression - Aldinucci, Donatella; Colombatti, Alfonso (Mediators of Inflammation, 2014)
Until recently, inflammatory chemokines were viewed mainly as indispensable “gate keepers” of immunity and inflammation. However, updated research indicates that cancer cells subvert the normal chemokine system and these molecules and their receptors become important constituents of the tumor microenvironment with very different ways to exert tumor-promoting roles. The CCR5 and the CCL5 ligand have been detected in some hematological malignancies, lymphomas, and a great number of solid tumors, but extensive studies on the role of the CCL5/CCR axis were performed only in a limited number of cancers. This review summarizes updated information on the role of CCL5 and its receptor CCR5 in cancer cell proliferation, metastasis, and the formation of an immunosuppressive microenvironment and highlights the development of newer therapeutic strategies aimed to inhibit the binding of CCL5 to CCR5, to inhibit CCL5 secretion, or to inhibit the interactions among tumor cells and the microenvironment leading to CCL5 secretion.